Sosialisasi Pemanfaatan Sampah Dan Penanaman Pohon Mangrove Desa Laulalang Kabupaten Tolitoli - Moh. Mudassir Ali; Ramdan Yusuf; Ramlah Ilham Darise (Universitas Negeri Gorontalo, 2023)
The importance of maintaining a clean and healthy environment is necessary to develop a character education program